Optimization of the production process for the anticancer lead compound illudin M: downstream processing - Lillibeth Chaverra-Muñoz; Theresa Briem; Stephan Hüttel (Microbial Cell Factories, 2022)
Abstract Background Secondary metabolites have played a key role as starting points for drug development programs due to their often unique features compared with synthetically derived molecules. However, limitations related to the discovery and supply of these molecules by biotechnological means led to the retraction of big pharmaceutical companies from this field. The reasons included problems associated with strain culturing, screening, re-discovery, purification and characterization of novel molecules from natural sources. Nevertheless, recent reports have described technical developments that tackle such issues. While many of these reports focus on the identification and characterization of such molecules to enable subsequent chemical synthesis, a biotechnological supply strategy is rarely reported. This may be because production processes usually fall under proprietary research and/or few processes may meet the requirements of a pharmaceutical development campaign. We aimed to bridge this gap for illudin M—a fungal sesquiterpene used for the development of anticancer agents—with the intention to show that biotechnology can be a vital alternative to synthetic processes dealing with small molecules. Results We used µL-scale models to develop an adsorption and extraction strategy for illudin M recovery from culture supernatant of Omphalotus nidiformis and these findings were successfully transferred into lab-scale. By adsorbing and eluting the product using a fixed resin-bed we reduced the working volume by ~ 90% and removed the aqueous phase from the process. After a washing step, a highly concentrated illudin M fraction was obtained by isocratic elution with 80% methanol. The fraction was dried and extracted using a water/heptane mixture, enriching illudin M in the heptane phase. From heptane illudin M could be instantly crystalized by concentrating the solution, achieving a final purity > 95%. Conclusion We have developed a robust, scalable and low-cost downstream process to obtain highly pure illudin M. By using solid phase extraction we reduced the production of solvent waste. Heptane from the final purification step could be recycled. The reduced amounts of solvents required, and the short purification time render this method a very economic and ecologic alternative to published processes.